Molecular mechanisms of enhanced expression of the chemokine interleukin 8 (CXCL8) in cystic fibrosis (CF) airway epithelial cells - Poghosyan, Anna (2014)
Cystic fibrosis (CF) is a fatal disease caused by a mutation of the CFTR gene and severe inflammation of the lungs. The inflammatory process is characterised by increased production of the potent neutrophil-attracting chemokine interleukin 8 (CXCL8), but the mechanism responsible is poorly understood. We tested the hypothesis that altered epigenetic regulation is responsible for the basal and cytokine-induced CXCL8 upregulation in CF airway epithelial cells. We found that CXCL8 protein levels and mRNA expression were higher in CF as compared to normal cells both basally and following cytokine stimulation. The difference in the expression was independent of increased mRNA stability or increased transcription factor activation and/or expression in CF cells. We found increased basal, but not cytokine-induced transcription factor binding to the CXCL8 promoter in a chromatin environment in CF cells in comparison with normal cells, increased histone H3 lysine 4 trimethylation, hypomethylation of CpG sites and increased binding of BRD3 and BRD4 to the CXCL8 promoter. Disruption of BRD4 association with chromatin using the selective BET bromodomain inhibitor JQ1 decreased CXCL8 protein release from CF cells to the levels observed in normal cells. Our observations suggest that epigenetic alterations are responsible for the upregulation of CXCL8 in CF and could become potential targets in the development of new therapeutic strategies.